PERANAN MEDIASI BELANJA PEMERINTAH DAN MODERASI AKUNTABILITAS KEUANGAN TERHADAP PEREKONOMIAN DAERAH - Hadiwibowo, Yuniarto; Priharjanto, Akhmad; Usman, Fadlil; Rakinaung, Ernest (Akurasi : Jurnal Studi Akuntansi dan Keuangan, 2023)
This research aims to analyze the effects of mediation of government spending and moderation of financial accountability in the regional economy. This research uses panel data analysis to estimate mediation of government spending and moderation of accountability for the regional economy with local original income, regional wealth, and quality of human resources as independent variables. This research also takes into account the impact of the Covid-19 pandemic on the regional economy. The population in this research is all districts/cities in Indonesia from 2013 to 2021. This research shows that government spending plays a mediating role in the regional economy and financial accountability plays a moderating role in the relationship between government spending and the regional economy. The results of this research also prove that local own-source revenue, regional wealth, quality of human resources, and the Covid-19 pandemic have an influence on the regional economy. The implication of this research is the importance of management of the local own-source revenue and financial accountability to support the regional economy.